2015
DOI: 10.1590/1981-863720150003000082908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different post-cure polymerization treatment on composite resin hardness

Abstract: Objective To evaluate the influence of different additional polymerization methods on the microhardness of two direct composite resins. Methods Direct Composite resins samples (Fill Magic and Opallis) and a Laboratory RESUMOObjetivo Avaliar a influência de diferentes métodos de polimerização complementar na microdureza de duas resinas compostas de uso direto. MétodosAs amostras foram confeccionadas com as resinas FillMagic, Opallis e Ceramage (Resina Composta Laboratorial); e fotopolimerizadas conforme recomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…Despite being controversial, some studies have shown a correlation between DC and hardness 12 , 13 , which can be explained by the fact that the strength of the material is determined not only by the inorganic fraction, but also by the creation of a dense, cross-linked polymeric network 12 . A base-to-top hardness ratio (B/T) ranging from 0.8 to 0.9 is an important criterion to verify the efficiency of polymerization in deeper areas in relation to the light source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being controversial, some studies have shown a correlation between DC and hardness 12 , 13 , which can be explained by the fact that the strength of the material is determined not only by the inorganic fraction, but also by the creation of a dense, cross-linked polymeric network 12 . A base-to-top hardness ratio (B/T) ranging from 0.8 to 0.9 is an important criterion to verify the efficiency of polymerization in deeper areas in relation to the light source.…”
Section: Discussionmentioning
confidence: 99%
“…This study used the same light source for all tests and resins, setting the same distance from the tip to the specimen and in the same work environment, in order to eliminate as far as possible any other variables that could affect the DC. Despite being controversial, some studies have shown a correlation between DC and hardness 12,13 , which can be explained by the fact that the strength of the material is determined not only by the inorganic fraction, but also by the creation of a dense, cross-linked polymeric network 12 . A baseto-top hardness ratio (B/T) ranging from 0.8 to 0.9 is an important criterion to verify the efficiency of polymerization in deeper areas in relation to the light source.…”
Section: Discussionmentioning
confidence: 99%
“…A busca por restaurações estéticas fez com que houvesse uma evolução nos materiais restauradores, surgindo assim as resinas à base de monômeros, como Bis-EMA, TEGDMA e UDMA 8,12,13 . A incorporação desses monômeros à formulação das resinas à base de Bis-GMA resulta em um aumento da resistência à flexão 12 .…”
Section: Discussionunclassified
“…At present, the demand for orthopedic treatment with fixed prostheses is increasing [1,2], taking place in the conditions of a consistently high level of aesthetic requirements of patients [3,4]. When choosing facing materials applied to the frameworks of fixed prostheses, their distinctive features and competitive advantages are assessed, including the economic benefits of the application, aesthetic qualities, physical and mechanical characteristics [5]. The last, in the indicated list, is the most significant, as the violation of the integrity of the prosthesis leads to its unconditional alteration.…”
mentioning
confidence: 99%